PERANCANGAN SISTEM ABSENSI BERBASIS QR CODE PADA MTs MUHAMMADIYAH PANYAKALAN - Lisa Annuriyah; Edwin Anwar; Jeprimansyah, Jeprimansyah; Etika Melsyah Putri (Nusantara Hasana Journal, 2025)
Attendance at MTs Panyakalan still uses a manual method, namely recording attendance on paper which will then be summarized from all attendance data, so it takes a long time. Therefore, a QR Code scan attendance information system is needed that can store attendance data more easily, help teachers in summarizing attendance data, and also make it easier for students and teachers to take attendance. In developing the existing system design at MTs Muhammadiyah Panyakalan, the waterfall method was used, this application was created using PHPMyAdmin for the database and the Visual Studio Code application as a tool to create the information system. This application helps the recording process automatically so that it is more effective and efficient.